Emotional Quotient dan Kaitannya dengan Kenakalan Remaja - Abd. Hakim (LP3M STITNU AL HIKMAH MOJOKERTO, 2022)
One important component of living in the midst of a community is the ability to manage emotions well. Goleman's research shows that only about 20% of the remaining 80% of IQ success is determined by a related factor called emotional intelligence. In fact, it can now be seen that a high IQ is not necessarily successful and not necessarily a happy life. People who have a high IQ but are emotionally unstable and short-tempered often fail to define and solve life's problems because of their inability to concentrate. Emotions do not grow, do not become overwhelming, often make changes when facing problems and deal with others with so much conflict. Emotions are less processed, they are easily controlled by others, who are sometimes very excited to agree on something, but turn into rejection in a short time, so it prevents the agreed cooperation with others. So the man failed. In Islamic education, great attention is paid to this. The mission of Islamic teaching is to guide and guide the growth and human development of students from one stage of life to another to achieve an optimal performance score. Pay attention to Islamic IQ and EI education, because Islamic education has a great impact on the growth of education, knowledge and intelligence.